2016
DOI: 10.1101/cshperspect.a018960
|View full text |Cite
|
Sign up to set email alerts
|

Computational Modeling of Adult Neurogenesis

Abstract: The restriction of adult neurogenesis to only a handful of regions of the brain is suggestive of some shared requirement for this dramatic form of structural plasticity. However, a common driver across neurogenic regions has not yet been identified. Computational studies have been invaluable in providing insight into the functional role of new neurons; however, researchers have typically focused on specific scales ranging from abstract neural networks to specific neural systems, most commonly the dentate gyrus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 68 publications
0
23
0
Order By: Relevance
“…Computer model results have suggested that the integration of adult-born neurons into a neural circuit results in neurogenesisinduced forgetting (Weisz and Argibay, 2012;Aimone, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Computer model results have suggested that the integration of adult-born neurons into a neural circuit results in neurogenesisinduced forgetting (Weisz and Argibay, 2012;Aimone, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the number of proliferating and, more importantly surviving neurons is critical in many hippocampal-dependent behaviours, including pattern separation [ 9 ]. The importance and integration of surviving neurons in these behaviours is a complex process [reviewed in 9 , 41 42 ]. Interventions to increase newborn granule cells in adults improves spatial and contextual discrimination [ 10 , 43 ], while ablating neurogenesis impairs discrimination behaviours [ 44 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicate that new neurons generated in the hippocampus could integrate into the preexisting neural circuits and are crucial for synaptic plasticity which is closely related to learning and memory (Christian, Song, & Ming, ; Deng, Aimone, & Gage, ; Kang, Wen, Song, Christian, & Ming, ; Leuner, Gould, & Shors, ; Sahay, Scobie, et al, ). Newborn neurons can regulate the pattern separation (Clelland et al, ; Sahay, Wilson, & Hen, ), mood (Sahay, Scobie et al, ), and other functions (Aimone, ; Apple, Fonseca, & Kokovay, ; Leuner et al, ). However, the mechanisms of regulating adult neurogenesis remain obscure.…”
Section: Introductionmentioning
confidence: 99%